Implementation of Data Warehouse in Human Resource Information System Using SEM-GeSCA - Muhammad Anshari; I Putu Suryadharma; I Wayan Rinas (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
Today, the changing nature of work and organization that occurs is quite high, causing the organization to be under pressure to adapt to changing circumstances. Work becomes more dynamic, making proactive behavior seen as a critical determinant of an organization's success. The purpose of this study was to identify the effect of HR practices on proactive behavior, as well as the role of mediation of work attachment to the relationship. Hypothesis testing using Generalized Structured Component Analysis model. From the test results found that the attachment of work plays a role in mediating the influence of work attachment to partial mediation behavior (Partial mediation). Limitations This study is using cross sectional data, a specific type of company and does not use data discriminately. This study uses dimensional integration to test proactive behavior that is directly influenced by HR practices and indirectly mediated by work attachment.